Patient data meta‐analysis of Post‐Authorization Safety Surveillance (PASS) studies of haemophilia A patients treated with rAHF‐PFM. (17th July 2014) - Iorio, A.; Marcucci, M.; Cheng, J.; Oldenburg, J.; Schoenig‐Diesing, C.; Matovinovic, E.; Romanov, V.; Thabane, L.
Summary: A Post‐Authorization Safety Study (PASS) global program was designed to assess safety and effectiveness of rAHF‐PFM (ADVATE) use in haemophilia patients in routine clinical settings. The main aim of this project was to estimate the rate of inhibitors and other adverse events across ADVATE‐PASS studies by meta‐analysing individual patient data (IPD). Eligible Studies : PASS studies conducted in different countries, between 2003 and 2013, for which IPD were provided. Eligible patients : haemophilia A patients with baseline FVIII:C < 5%, with a known number of prior exposure days (EDs). Primary outcome : de novo inhibitors in severe, previously treated patients (PTPs) with > 150 EDs. Secondary outcomes : de novo inhibitors according to prior exposure and disease severity; other adverse events; annualized bleeding rate (ABR). Analysis : random‐effects logistic regression. Five of seven registered ADVATE‐PASS (Australia, Europe, Japan, Italy and USA) and 1188 patients were included (median follow‐up 384 days). Among severe PTPs with > 150 EDs, 1/669 developed de novo inhibitors (1.5 per 1000; 95% confidence interval [CI] 0.2, 10.6 per 1000). Among all patients included in the PASS studies, 21 developed any type of inhibitors (2.0%, 95% CI: 0.8%, 4.7%). Less than 1% of patients presented with other serious adverse events possibly related to ADVATE. The overall median ABR was 3.83 bleeds/year (first, third quartiles: 0.60, 12.90); 1.66 (0, 4.78) in the 557 patients continuously on prophylaxis ≥ twice/week. Meta‐analysing PASS data from different countries confirmed the overall favourable safety and effectiveness profile of ADVATE in routine clinical settings.